Familiarizing the Alien: Designing working nodes that reveal the opportunity of invasive alien plants as a resource in the Theewaterskloof catchment area - Suijs, Yvo Cornelis Adrianus (School of Architecture, Planning and Geomatics, 2021)
The Theewaterskloof dam supplies more than 40% of the City of Cape Town's water. However, the catchment area that leads to the dam is almost entirely infested with invasive alien plant species which are the single largest contributor to water loss from the dam (up to ±300 million liters of water are lost per year). Given the context of severe water scarcity in the region, the management of these alien invasive species, which are rapidly spreading, must become a priority. This thesis investigates how landscape architectural design can influence management strategies for dealing with the alien plant invasion of mountain catchments, and how these alien species may come to be seen not just as a threat, but also as a resource. The project examines mechanisms of invasiveness in four key plant species affecting the area in order to inform a suitable responsive management strategy. Mapping of the current locations of invasive alien plants, their context-specific growth patterns and densities was required. An analysis of how these four species could be used in the production of timber, wood fuel, resin, honey and carbon products, reveals significant potential for using these invasive plants as an economic resource. One of the key discoveries of the research, is that access to invaded mountain areas, which include steep, rugged and marshy terrains, remains a major obstacle to the management of the invasive alien plants. The design project considers a system for improving access to these difficult-to-reach areas which doubles as a system of new recreational routes through the landscape. As part of the public interface with the productive and management systems that are envisioned, an experimental working node is developed. The node combines productive and experiential programs in an engaging public space that aims to change perceptions that acknowledge the presence of alien invasive plants as an enduring feature of the landscape.